Synthesis, spectroscopic and nonlinear optical properties of metal-free and nickel Î² substituted binuclear phthalocyanines - Kabwe, Kapambwe Peter (Rhodes University, Faculty of Science, Department of Chemistry, 2016)
In this project, nickel and metal-free 4Î²-(4-tert-butylphenoxy) phthalocyanine, biphenyl bridged binuclear 4-tert-butylphenoxy phthalocyanine and naphthalene bridged binuclear 4-tert-butylphenoxy phthalocyanine have been synthesised. The Z-scan technique has been employed to comparatively study their second order nonlinear optical (NLO) properties. This work, shows that the presence of H-aggregation in binuclear Pcs of metal-free and nickel 4Î²-(4-tertbutylphenoxy) phthalocyanines do not have an effect on the magnitude of second order nonlinear absorption coefficient (Î²) as compared to monomeric Pcs. Density functional (DFT) calculations of dipolar/octupolar contributions were performed, in order to explain experimentally determined Î² values. Spectroscopic and photophysical properties of the synthesised compounds have been determined using a range of different spectroscopic techniques, including magnetic circular dichroism (MCD), time correlated single photon counting spectroscopy (TCSPC), UV-visible absorption spectroscopy, mass spectroscopy and IR Spectroscopy.
Keywords: Uncatalogued